The Representation of Neonatal Emergency Obstetric Care Management Base (PONED) In Gorontalo District Tibawa Health Centers - Franning Deisi Badu; Fitria Saleh (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2017)
Background: Development of Community Health Centers capable PONED that is part of the MPS which began in 2009, beginning with the training of doctors, nurses and midwives as well as complementary facilities and infrastructure on the terms that have been set were expected to prevent and manage complications of pregnancy and childbirth so be able to reduce MMR and IMR. The purpose og this research is to find out information about the implementation of Emergency Obstetric Care and Neonatal Basic (PONED) in Tibawa Health Centers 2016. Methods: This Research used qualitative research was to obtain in-deph information (in-deph-Interview) on management of the implementation (PONED) in rural community of Tibawa Health Centers 2016 sample size consisted of three people, divided into key informants and common informant. Results: PONED own with good planning, because the planning has been carried out every year. Organizing PONED has made the division of tasks and organizational structures that standard. PONED implementation in the field still had shortcoming, for the reason that a trained midwife PONED not all exposed areas of training MPS (Management Pregnancy Saver). Supervision is good, because the leader oversight had been monitoring on a regular basis at the Community Health Center. Evaluation was good quality, because the health department regularly conducted supervision through the evaluation of SPM (Minimum Service Standards) which is done every three months and every year. Suggestion: The health department would be able to think of the addition of qualified helath professionals such as midwives are sufficient for basic emergency care and trained nurses. Keywords: Planning, Organizing, Implementing, Monitoring and Evaluation